Pemanfaatan Media Pembelajaran Wordwall untuk Meningkatkan Hasil Peserta Didik Materi Organ Pernapasan Hewan Kelas V SDN 1 Kedungkumpul Sukorame Lamongan - Ainnun Qaidhar Junioviona (LP. Ma'arif Janggan Magetan, 2022)
From the observation that has been done in Kedungkumpul 1 Elementary School.Learning result of the stundents are low. This matter is caused because lack of learning media and learning model usage during the learning process in the class room. This problem could be overcome by utilize Wordwall Web Application as a media that appropriate with students learning characteristics so it may increase students learning motivation. The purpose of this research is to describe students and teacher activity improvements and also improvement of student learning results that involve cognitive aspects with wordwall web application used as a learning media that used to evaluation questions which are expected to increase the attractiveness of students to learning materials. This research is done using Class Action Research Location of this research is in Kedungkumpul 1 Elementary School. The research subject is the teacher and students Grade Fifth Kedungkumpul 1 Elementary School Sukorame Lamongan that has been done in 2 cycle. Each 1 cycle is consist of 3 stage/step, that is planning stage, implementation stage, and observation and reflection stage. The data collection is using teacher activity observation sheet, students activity observation sheet and students learning results assessment. The results of this research shows that the activity of the teacher is improved by 22%, while students activity is increased by 25%. In students learning results from the three aspects also show improvement, in cognitive aspects is increased 16,3. Based on results of the research that have been obtained, it could be concluded that the Wordwall Application Web as a evaluations media with my residence theme able to increase learning results of Grade V students in Kedungkumpul 1 Sukorame Lamongan